Λιτανεία Ιερού Λειψάνου και Εικόνας Αγίου Χριστοφόρου 2018 (ΔΗΜΟΣ ΑΓΡΙΝΙΟΥ ΤΜΗΜΑ ΠΛΗΡΟΦΟΡΙΚΗΣ, 2018)
: Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε! Βαστείτε!